Carotid artery modeling using the Navier-Stokes equations for an incompressible, Newtonian and axisymmetric flow - Fojas, Jhalique Jane R. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
This paper describes two dimensional (2D) model of the cardiovascular system (CVS) using computational software (CS). Simplification with respect to a particular vascular area of interest was done, and blood was considered as an incompressible Newtonian fluid. Structural modeling of the carotid arteries about the bifurcation area was constructed from computed tomography (CT) scan images using computer-aided design (CAD). The numerical technique utilized was Arbitrary Lagrangian Eulerian (ALE) which was introduced in a finite element system. The Eulerian reference was applied for the fluid domain, while the Lagrangian formulation was used for the structure domain. Coupling of the reference systems was carried out on arbitrary computational grid permitting numerical modeling of hemodynamics as governed by 2D axially symmetric incompressible Navier-Stokes equations (NSE).
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Cardiovascular system; Blood flow; Hemodynamics; Blood -- Circulation